Bladder wall tension during physiological voiding and in patients with an unstable detrusor or bladder outlet obstruction - Bross, Stephan; Braun, Peter-Martin; Michel, Maurice Stephan; Jünemann, Klaus-Peter; Alken, Peter (BJU international, 2003)
OBJECTIVE To develop and evaluate a new clinical method for measuring bladder wall tension (BWT) on detrusor contraction during physiological voiding and under pathological conditions, as in experimental trials during subvesical obstruction the ability to generate pressure increases, whereas the contractile force per cross-sectional area of detrusor muscle decreases. PATIENTS AND METHODS In all, 24 patients were divided into three equal groups: group 1 (mean age 58, sd 8.6 years) comprised men with bladder outlet obstruction in accordance with the Abrams-Griffiths nomogram; group 2 (four men and four women, 56, sd 7.2 years) had detrusor instability; and group 3 (54, sd 9.6 years) had normal bladder emptying. BWT, as the detrusor force per cross-sectional area of bladder tissue (in N/cm2), was calculated after a urodynamic evaluation and ultrasonographic estimate of bladder wall thickness. RESULTS In all patients it was possible to measure BWT; the mean (sd) maximum BWT in group 1 was 9.8 (3.9) N/cm2, in group 2 during bladder instability was 11.7 (2.6) N/cm2 and in group 3 was 2.8 (0.5) N/cm2. CONCLUSIONS Estimating BWT in humans is possible by combining a urodynamic evaluation with an ultrasonographic estimate of bladder wall thickness. Further clinical research should elucidate the clinical relevance of BWT under comparable conditions.
Gesehen am 08.03.2022